Manufaktur Cakram Motor 150cm³ dengan 3 Lubang, Diameter Luar 200mm, Tebal 4mm, Kapasitas 2 Biji/Jam - Lailatul Hidayah; Syamsul Hadi; Oliver Mirza Safrilullah; Bima Gananta Ale Majid; Muchammad Tiffa Taufiqur Rachman (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The 4 stroke, 150 cm³, 2003 motorcycle brake disc product with 3 holes, 200 mm outer diameter, 4 mm thick is no longer produced by the factory due to the problems faced. The manufacturing goal is to obtain a 150 cm³ motorcycle disc with 3 holes, 200 mm outer diameter, 4 mm thick in order to meet the needs of brake disc products in the market. The brake disc manufacturing method includes: motorcycle brake disc design, selection of medium carbon steel raw materials, AISI 1045, cutting raw materials with a welding flame from 1.5 m x 2 m x 5 mm plate material to 205 x 205 x 5 mm, making center holes with a drilling machine in stages to 56 mm, turning two sides to a diameter of 201 mm x 4.1 mm, drilling 3 holes with a diameter of 8 mm with a radius of 110 mm at an angle of 120o, grinding two sides each 0.5 mm with a roughness of N7 or 1.6 m, and checking the quality and dimensions of the product. The manufacturing results are in the form of brake discs made of AISI 1045 material with an outer diameter of 201 mm, a thickness of 4 mm, a surface roughness of Ra 1.48 um, with 3 M8 bolt holes, a total production cost of IDR 125,000/unit, and a fabrication duration of 24 minutes/unit, which implies that a 4-stroke, 150 cm³, 2003 motorcycle can be re-used using brake discs that meet its specifications.